When The Earth Lost Its Shapes - Shobha Viswanath; Christine kastl (Chennai : Karaditales Comapny Pvt. Ltd., 2008)
When all the shapes in the world disappear, it is up to the little dot to bring them back and restore order.
Fiction.
Keywords: Earth (Planet).; Fiction Shape Fiction